2015
DOI: 10.1155/2015/671349
|View full text |Cite
|
Sign up to set email alerts
|

On the Estimation of Heritability with Family-Based and Population-Based Samples

Abstract: For a family-based sample, the phenotypic variance-covariance matrix can be parameterized to include the variance of a polygenic effect that has then been estimated using a variance component analysis. However, with the advent of large-scale genomic data, the genetic relationship matrix (GRM) can be estimated and can be utilized to parameterize the variance of a polygenic effect for population-based samples. Therefore narrow sense heritability, which is both population and trait specific, can be estimated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 22 publications
1
16
0
1
Order By: Relevance
“…In addition, we selected EBV VCA‐IgA, given its reported familial correlations, 21 to estimate its heritability and to adjust VCA‐IgA levels as an additional covariate for heritability estimates of NP EBV loads. For height and body mass index (BMI) the heritability was estimated as well to verify the validity of these analyses given their reported high heritability and the multiple identified genetic susceptibility variants 22‐24 …”
Section: Methodsmentioning
confidence: 99%
“…In addition, we selected EBV VCA‐IgA, given its reported familial correlations, 21 to estimate its heritability and to adjust VCA‐IgA levels as an additional covariate for heritability estimates of NP EBV loads. For height and body mass index (BMI) the heritability was estimated as well to verify the validity of these analyses given their reported high heritability and the multiple identified genetic susceptibility variants 22‐24 …”
Section: Methodsmentioning
confidence: 99%
“…Polygenic variance is estimated using the kinship coefficient matrix, using the same mathematical principles as recently developed heritability estimation methods for unrelated subjects (Yang et al, 2010). A further description of these methods can be found in Kim et al (2015). Thus, we used structural equation modelling (SEM) to partition spelling at each age level into heritable components, random environmental components, and the influence of SES.…”
Section: Methodsmentioning
confidence: 99%
“…Because the twin study that reported 88.5% heritability of measles vaccination response was from the same Rochester, MN, community as the population-based sample used in this study, large environmental differences are not likely to explain the difference in heritability estimates. It is known, however, that twin studies can give inflated estimates of heritability when twins share more environment than distantly related subjects [33]. This raises the question of whether the earlier twin study overestimated the heritability of response to measles vaccination.…”
Section: Discussionmentioning
confidence: 99%